Discourse on the Civil Rights of the Deaf People in Making a Notary Deed - Kumala, Ida Ayu Ratna; Sudantra, I Ketut (Udayana Journal of Law and Culture, 2023)
It is generally said that disabled persons do not have proper access to justice and are not treated equally before the law. In Indonesia, the human rights approach has been incorporated into developing laws and policies for disabled persons. However, disabled people still face legal difficulties. This article aims to discuss the legal capacity of a deaf person to perform the legal action of making a deed before a notary in Indonesia from the perspectives of human rights, contracts, and notary laws.   It reflects legal research that uses a statutory and conceptual approach. Primary legal materials are obtained from the national laws and regulations of Indonesia and relevant international legal instruments, while secondary legal materials are obtained from books, journal articles, and website content. The findings reveal that Indonesian national law generally recognizes the right of persons with disabilities, including deaf people, to perform civil law actions. In general, deaf people can sign a contract; however, there is no guarantee that they understand the communication process in making a deed. In this context, there are still obstacles related to the lack of sign language interpreters in Indonesia, which can complicate the transferring of information when making notarial deeds between deaf clients, notaries, and witnesses.